Deletion of Mgat2 in spermatogonia blocks spermatogenesis - Asmat, Mohd Shamoon; Zheng, Xiang Yu; Nauman, Mohd; Zheng, Deyou; Stanley, Pamela (Frontiers in Cell and Developmental Biology, 2024)
Identifying factors required for spermatogenesis is important for understanding mechanisms of male fertility. Inactivation of either the Mgat1 or Man2a2 gene leads to a block in spermatogenesis causing infertility in male mice. MGAT1 GlcNAc-transferase initiates complex N-glycan synthesis and MAN2A2 mannosidase generates the substrate for MGAT2 GlcNAc-transferase to form a biantennary complex N-glycan. In this paper we show that conditional deletion of Mgat2 in spermatogonia via Stra8-iCre caused a novel block in spermatogenesis, largely prior to the formation of round spermatids. Mgat2[-/-] germ cells did not bind the lectins Phaseolus vulgaris leukoagglutinin (L-PHA) of Griffonia simplicifolia II (GSA-II)L-PHA or GSA-II, similar to germ cells lacking MGAT1 and complex N-glycans. However, overall spermatogenic defects were distinct in germ cells following deletion ofwith deleted Mgat2 versus Mgat1 in germ cells. In addition, RNA-seq analysis at 15 days after birth revealed a unique transcriptomic landscape in Mgat2[-/-] germ cells with genes required for sperm formation and functions being most down-regulated. Bioinformatic analyses using the Ingenuity Pathway Analysis (IPA) algorithm identified ERK and AKT as central activities. Western blot analyses of 15-day germ cell lysates confirmed that both AKT and ERK1/2 signaling were increased by loss of MGAT2 in germ cells. By contrast, Mgat1[-/-] germ cells were previously shown to have reduced ERK signaling and unchanged AKT activity. Therefore, sincewhile the loss of all complex N-glycans is common to each mutant model, the different spermatogenic defects observed appear to arise from the different immature N-glycans that accumulate in Mgat2[-/-] versus Mgat1[-/-] germ cells are proposed to be the basis of their unique spermatogenic phenotypes..